Fetal and Abortion Rights Under the Maastricht Principles on the Human Rights of Future Generations: a Contradiction - Aguocha, Chinedu Collins (Journal of Legal Studies, 2025)
On 3 February 2023, the Maastricht Principles on the Human Rights of Future Generations was adopted in Maastricht, Netherlands, by a group of human rights experts.  Though not legally binding, these Principles seek to safeguard the rights of persons, groups, and peoples yet to exist. Accompanying the Maastricht Principles is a Commentary by the drafters explaining the import of each principle. This paper argues that the categorical denial of any form of legal protection for human embryos, fetuses and unborn children in the Maastricht Principles fundamentally undermines its objective and conflicts with the Convention on the Rights of the Child (CRC). It posits that women’s reproductive rights, including abortion, must be balanced with the imperative to protect the survival of unborn children. It juxtaposes the pro-life and pro-choice views on abortion, highlighting untapped middle grounds. While acknowledging that the mother's best interests should prevail in cases of conflict, this paper asserts that granting human embryos and fetuses a baseline of legal protection is essential to the coherence of the Maastricht Principles. Without such safeguards, the very concept of future generations is jeopardized.